A mini review on phytoremediation of fluoride-contaminated waters: a bibliometric analysis - Vaz, Lucas Rafael Lommez; Conesa, Juan Antonio; Borges, Alisson Carraro (Frontiers in Environmental Science, 2023)
Traditional techniques for removing fluoride (F-) from water are costly, whereas phytoremediation is a less expensive method that can be adopted as a tool to control not only fluorine, but also other pollutants in watersheds. Phytoremediation as a strategy for defluoridation is little used and still has a long way to go. Therefore, it is important to get a picture that describes achievements and trends around this topic and support decision-making processes to move forward. The aim of this study was to collect bibliometric data on the use of phytoremediation to remove F-. Data collected considered the scenario of related publications regarding countries, researchers, chronological evolution of the publications, co-occurrence of terms to point out overall focus and interests of researches and collaboration initiatives around the subject. India has the highest number of publications on F- phytoremediation, which can be explained by the high incidence of fluorosis in that country. The number of publications, although still small, has grown over the last five years. A cluster map showing the co-occurrence of terms indicated research on the effects of F- on plant metabolism, and the correlation of this contaminant when in the presence of heavy metals and with issues of sanitation. Different studies also seek species of accumulator plants, and investigate physical and chemical parameters of the environment that influence the absorption of the F- anion. New approaches to optimize the process and phytoremediation overall are on the rise like the use of phytohormones, growth-promoting bacteria, sorption processes and genetic manipulation